Co-Curricular Management of Islamic Programs to Form Student Discipline - Lutfi, Muhammad; Perawironegoro, Djamaluddin; Yoyo, Yoyo; Astari, Rika; Hopid, Abdul (Journal of Indonesian Progressive Education, 2025)
This study examines the management of Islamic co-curricular programs in shaping student discipline at SMA Muhammadiyah 3 Yogyakarta. The research is motivated by the importance of student discipline in supporting the success of educational processes, particularly within Islamic co-curricular activities. In practice, however, the implementation of Islamic programs has not fully achieved the expected outcomes in developing disciplined student behavior. Although activities such as daily Qur’anic recitation, weekly tasmi’ Al-Qur’an, and Islamic boarding programs have been routinely conducted, students’ responses and levels of discipline remain varied. Some students perceive the programs as less organized, less engaging, and not fully connected to the development of disciplinary values. This research employed a qualitative approach using observation, documentation, and in-depth interviews with purposively selected informants, including school leaders, ISMUBA teachers, and students. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and technique triangulation. The findings indicate that the management of Islamic co-curricular programs has been implemented systematically and contributes significantly to shaping student discipline through moral knowledge development, the creation of a conducive moral environment, and the habituation of disciplined behavior. Overall, Islamic co-curricular management is effective in fostering student discipline through educational guidance, exemplary practice, and continuous habituation.